SITUS-SITUS MEGALITIK DI KABUPATEN BONE: KAJIAN SEBARAN DAN KRONOLOGI - Bernadeta AKW (Balai Arkeologi Provinsi Sulawesi Selatan, 2018)
Megalithic culture research at Labuaja Site, Kahu sub-district and other sites in Bone Regency aims to determine the distribution and chronology. This research doing by survey and excavation techniques. Archaeological data found from megalithic sites in Bone Regency are presented in descriptive analysis. In addition, C14 analysis was also carried out with charcoal in Beta Analytic Inc. Miami, Florida, USA to find out its absolute date. The results showed that megalithic sites in Bone had a fairly even distribution and occupy the slope to hilltops with a height of 28 - 218 meters above sea level. The results of radiocarbon dating indicate that the age of the site and megalithic culture in Labuaja, Bone ranges from 400 - 190 BP (around the 15th-17th century AD). Based on that date, the megalithic culture in Labuaja began in the golden age of the kingdom of Bone. Megalithic culture in Bone has associations with natural resources such as rivers and rice fields which are very supportive in the activities of human life that depend on agricultural resources. With the exploitation of agricultural resources, thus produce the social system and ideology adopted by the people who reach the Islamic period. Penelitian kebudayaan megalitik pada situs Labuaja, Kecamatan Kahu dan situs-situs yang lainnya di Kabupaten Bone bertujuan untuk mengetahui sebaran dan menentukan kronologinya. Penelitian ini dilakukan dengan teknik survei dan ekskavasi. Data arkeologis yang ditemukan dari situs situs megalitik di Kabupaten Bone disajikan dalam bentuk deskriptif analisis. Selain itu, dilakukan pula analisis C14 dengan bahan arang di Beta Analytic Inc Miami Florida, USA untuk mengetahui pertanggalan absolutnya. Hasil penelitian menunjukkan bahwa situs-situs megalitik di Bone memiliki sebaran yang cukup merata dan menempati wilayah lereng hingga puncak bukit dengan ketinggian antara 28 – 218 meter di atas permukaan laut. Hasil pertanggalan radiokarbon menunjukkan bahwa umur situs dan kebudayaan megalitik di Labuaja, Bone berkisar antara 400 – 190 BP (sekitar abad ke-15–17 Masehi). Berdasarkan pertanggalan tersebut, kebudayaan megalitik di Labuaja berawal pada zaman keemasan kerajaan Bone. Kebudayaan megalitik di Bone memiliki asosiasi dengan sumber-sumber alam seperti sungai dan persawahan yang sangat menunjang dalam aktivitas kehidupan manusia yang bergantung pada sumber sumber pertanian. Dengan kegiatan eksploitasi sumber pertanian, sehingga melahirkan sistem sosial dan ideologi yang dianut oleh masyarakat yang menjangkau periode Islam.